EFEKTIVITAS PEMBELAJARAN DARING DITINJAU DARI MOTIVASI BELAJAR DAN KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA - Moh. Supratman; Saiful Padli (LPPM Institut Pendidikan Nusantara Global, 2021)
This study aims to determine the effectiveness of online learning in terms of students' motivation and creative thinking skills in mathematics. This type of research is a qualitative research with a descriptive approach. This research was conducted at SMK Qamarul Huda Bagu by useing online with the research subject being class XI. The instrument used is a motivational questionnaire and mathematical creative thinking skills in online learning. The questionnaire was conducted by making questions that were distributed to all respondents in the form of a google form. Based on the results of descriptive statistical analysis of student learning motivation data on mathematics presented in the table above, it shows that the average student learning motivation before online learning is 101.81. While the average student learning motivation after online learning is 119.43. This shows that there is an increase in students' learning motivation before and after online learning. While the effectiveness of learning with individual learning completeness is on average 85.65, the ability of teachers to manage learning is on average 89.81, and student responses are 80.28. From these data it can be concluded that online learning is effective in increasing students' motivation and creative thinking skills.